Stereotip gender dalam penggunaan bahasa: Mitos atau fakta? - Hotimah, Emah (Maliki Interdisciplinary Journal, 2024)
Language, as a vital communication tool in human life, is not immune to the influence of gender stereotypes. These stereotypes, in the form of rigid assumptions based on gender, are seen in the different ways men and women speak, write and use non-verbal language. Not only do they shape social perceptions, but they also impact everyday interactions and power dynamics in society. This article examines the myths and facts of gender stereotypes in language. Myths such as women are more talkative and men are better at science are debunked with scientific evidence. Research shows that the difference in the number of words spoken by men and women is not significant, and intellectual ability is not bound by gender. Differences in language styles between men and women are recognized, but stereotypes reinforced by media and popular culture often have negative impacts, such as reinforcing gender discrimination, limiting career choices and opportunities, and causing miscommunication and conflict. Towards an equal and inclusive language, it is important that we avoid using discriminatory words, adopt language that is polite and respectful of differences, and educate people about the negative impact of gender stereotypes. By doing so, we can build a culture of communication that is more equitable and free from gender bias, reflecting the values of equality and inclusivity in our daily interactions.